Institutional Arrangements for Transport Corridor Management in Sub-Saharan Africa - Adzibgey, Yao; Kunaka, Charles; Mitiku, Tesfamichael Nahusenay (World Bank, Washington, DC, 2014)
Corridor efficiency is important to the competitiveness of most of the African economies, especially those that are landlocked. Corridors can be defined as a collection of routes linking several economic centers, countries and ports. While some are only road transport corridors, most of them include more than one mode of transport. The Sub-Saharan Africa Transport Policy Program (SSATP) places emphasis on the facilitation of inter-state trade along corridors. It particularly focuses on identifying impediments to the efficient movement of traffic and seeks to promote appropriate strategies for minimizing hurdles to such movement. This objective is also consistent with the Millennium Development Goals (MDGs) and the Almaty Plan of Action. This concept paper reviews the legal and institutional options for establishing corridor management groups and proposes a framework for establishing such groups along all major transport corridors. Some of the lessons have emerged from the existing corridor management arrangements: (i) corridor groups interventions are problem solving and the operational procedures should encourage this objective and retain flexibility necessary to be responsive; (ii) working groups can be formed on an ad hoc basis to address specific issues and disbanded once the objective met; and (iii) the group organization should ensure public-private interaction at all levels. A three-tier corridor management institution is proposed for regional transport corridors without any arrangement. The institutional hierarchy would comprise a stakeholders group, a core group and a secretariat. Funding arrangements for existing corridor groups include membership fees, contributions by governments, traffic-based usage fees, or donor support. Generally, the funding mechanism of a corridor group would be influenced by its legal instrument. Once established, the group would be able to develop an action plan and deliver some results making it possible to introduce a usage-based funding mechanism such as a tonnage levy.